WATER METHOD PREGNANCY EXERCISES TO REDUCE PREGNANCY BACK PAIN AQUATIC GYMNASTICS - Satriawan Chan, A. Apri; Suardi, Sandy; Hidayat, Arif (Dharmas Journal of Sport, 2024)
Ten percent of pregnant women have chronic pain, and up to fifty percent have back discomfort. As the six-month mark approaches, 80% of pregnant women will at some point feel back pain, which is mostly due to changes in the spinal muscles (70%). Compared to weight-bearing exercise without the water method, the water pregnant exercise method is more strenuous and has a lower failure rate. Because they are submerged in water, this exercise improves thermoregulation and gives them a sense of lightness and comfort when moving. In addition, hydrostatic pressure may be able to prevent and treat lower back pain and lessen edema.